2017
DOI: 10.1055/s-0042-118828
|View full text |Cite
|
Sign up to set email alerts
|

Anästhesie und Outcome: Einfluss der perioperativen Prozesse

Abstract: In recent years, the role of the anesthesiologist has turned tremendously from the "anaesthesia doctor" into a perioperative physician and risk specialist. Patients are older, multimorbid, and are called up for more and more extensive surgery and interventions. Socioeconomic aspects have grown in importance. The anesthesiologist, paving the way for a good outcome, is involved in nearly all perioperative processes: preoperative evaluation, definition and optimization of preoperative and intraoperative condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…A correct Chinese translation as "麻醉医师" or "围 术期医生" should be introduced and extended to both patients and medical staff. 12 We found that urban patients, those aged younger than 65 years old, and those received college or above education, or with medical education background had statistically significant better understanding about anesthesiologists' job nature, which was similar to results in previous studies. 1 Most patients in this survey knew some of intraoperative responsibilities that anesthesiologists have, such as putting patients to sleep (66.6%) and waking patients up (74.7%).…”
Section: Discussionsupporting
confidence: 89%
“…A correct Chinese translation as "麻醉医师" or "围 术期医生" should be introduced and extended to both patients and medical staff. 12 We found that urban patients, those aged younger than 65 years old, and those received college or above education, or with medical education background had statistically significant better understanding about anesthesiologists' job nature, which was similar to results in previous studies. 1 Most patients in this survey knew some of intraoperative responsibilities that anesthesiologists have, such as putting patients to sleep (66.6%) and waking patients up (74.7%).…”
Section: Discussionsupporting
confidence: 89%
“…In the recent years, the role of the anesthesiologist is turning from the 'anesthesia doctor' to the perioperative physician and risk specialist [7]. The anesthesiologist is involved in the preoperative evaluation, definition, and optimization of preoperative and intraoperative conditions, management of modern intraoperative anesthesia as well as postoperative high complex patients.…”
Section: Introductionmentioning
confidence: 99%